Hak Asasi Manusia; Studi Komparatif antara Orientasi Kebebasan Manusia Perspektif Buddhisme dan Islam - Untung, Syamsul Hadi; Sakti, Mohammad Djaya Aji Bima (Jounal Nyanadassana, 2023)
Human Rights is a discourse that has several orientations on issues around humanity. One of the elements in the formulation and ratification of human rights in this law is to guarantee that every individual has freedom of will and action in their lives. However, the desired orientation of freedom in this formulation experiences several problems, including confusion in understanding the meaning of freedom itself, many of the world's scientists provide a variety of different perspectives on the meaning of the discourse. In addition, the aridity of religious elements is also felt in the formulation of human rights, so it is necessary to understand aspects of human freedom from several perspectives, such as Islam and Buddhism, two religions that have a concept of humanity and a philosophy of several elements related to this concept. Islam and Buddhism have two concepts related to the freedom orientation above, Insan Kaamil in Islam and Bodhisattva in Buddhism. These two things will be observed with a theological approach and comparative method so that basic conclusions will be obtained on the concept of man and freedom in the two religions and an analysis of the relationship between the concepts of freedom in Islam and Buddhism.